Investigating University Students’ Learning Habits in the Digital Era: A Preliminary Survey Study - Adawiah, Robiatul; Aulia, Aulia; Lutfiatussolihah, Lutfiatussolihah; Miratunnisah, Miratunnisah; Gunawan, Gunawan (Indonesian Journal of Teacher Education, 2025)
The rapid advancement of digital technology has significantly transformed university students' study patterns, particularly regarding information access and learning strategies. This preliminary survey study aims to explore students' learning habits in the digital era and identify the benefits, challenges, and strategies employed in managing technology-based learning. This study employed a quantitative approach with a descriptive survey design, involving 65 students from various universities, who were selected using convenience sampling. Data were collected using an instrument comprising Likert scales, multiple-choice options, checklists, and short-answer questions. The results indicate that students perceive digital learning positively, with most mean scores exceeding 3.00. Key findings include high scores for using the internet for supplementary explanations (3.98), learning flexibility (3.91), and rapid comprehension via gadgets (3.68). Many respondents reported studying for 1–2 hours daily (47.7%) and identified Google Scholar (44.6%) and YouTube (40%) as their primary learning resources. Smartphones were the most commonly used devices (61.5%), while home or boarding houses were the preferred locations for study (81.5%). The most significant advantages cited were ease of access to materials (73.8%) and time flexibility (70.8%). However, students faced challenges, primarily concentration distractions from notifications and social media (56.9%) and unstable internet connections (56.9%). To maintain focus, the most common strategies were limiting smartphone usage (55.4%) and establishing a regular study schedule (47.7%). Overall, digital learning is considered effective if students can effectively manage their devices, time, and learning environments. These findings provide a comprehensive overview of student study patterns and offer a foundation for developing more adaptive digital learning strategies in higher education.